Multiple acute aortic dissection in a young adult. - Kosai NR; Reynu R; Abdikarim M; Jasman MH; Taher MM; Idris MA; Harunarashid H (Penerbit UKM, 2014)
The diagnosis of aortic dissection in a young adult in the absence of atherosclerosis or prior history of trauma is extremely rare. The presence of more than one arterial dissection site in such a patient is even more unheard of. We highlight a case of spontaneous multiple acute arterial dissections occurring in a 32-year-old male. Stanford B aortic dissection and a separate dissection extending from the bifurcation of the right common iliac artery to the right common femoral artery was noted on computed tomographic angiography (CTA). A small aneurysm of the right subclavian artery was also noted. A two-stage hybrid procedure involving a combination of open and endovascular surgery was employed. The rarity and lethality of this condition warrants a high index of suspicion for early diagnosis and prompt intervention.